Competency mediates the influence of talent, interpersonal skills, and motivation on work ethic in entrepreneurial students - Kusnilawati, Nunik; Kuswardani, D. C.; Utaminingsih, Adijati; Sulistyawati, Ardiani Ika; Kusuma, Linda (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
Work ethic is currently a strategic entrepreneurship issue. Gaps were still found in previous studies. This study uses an alternative research model by placing the competency variable as a mediating variable. Such a model is the novelty of this research. The research aims to analyze the influence of talent, interpersonal skills, and motivation variables on work ethic through competency mediation in entrepreneurial students in Semarang. This research uses a sample of 120 respondents. Data was collected using a questionnaire instrument and distributed to respondents via Google Forms. The measurement scale uses a Likert scale with five response points. This research processed data using SmartPLS, starting with validity and reliability tests, then descriptive statistical analysis, and ending with inferential analysis. This study uses a significance-level test to test the hypothesis. Valid and reliable data can be identified through validity and reliability tests. The analysis results show that work ethic is influenced by 62 percent by the interpersonal skills-motivation variable, while competence is influenced by 59 percent by the talent-interpersonal skills-motivation variable. The results show that competence plays a role as a mediation between interpersonal skills and work ethic, as well as between motivation and work ethic, but does not mediate between talent and work ethic.